Managing capital flows: The case of Viet Nam - Vo Tri Thanh; Pham Chi Quang (Asian Development Bank Institute (ADBI), 2008)
Thanks to reforms and international integration, Viet Nam has recorded impressive economic development achievements. Deepening integration and accession to the WTO has brought about both new opportunities and challenges to a country on its way to accelerating reform and development. The recent surge in capital inflows has led to a financial boom in Viet Nam as well as risks, especially in the context of macroeconomic policy inconsistencies, weaknesses in the banking sector and financial supervision. The macroeconomic policy responses so far (up to February 2008) seem to be less effective in stabilizing the economy and in reducing policy inconsistencies as well as financial risks. The key question for Viet Nam, now, is how to sustain economic growth and sound financial development while mitigating possible financial risks. This paper recommends a broad reform package including tackling the bottlenecks in the economy (the weaknesses of economic institutions, infrastructure, and human resources), modernizing the State Bank of Vietnam (SBV), and strengthening risk management in the banking sector and financial supervision system. The focus is also on capital market development based on improvement of its fundamentals and the reform of large state-owned corporations. In particular, this paper argues for having a firm commitment to combating high inflation and combining tightened monetary policy with a more flexible exchange rate and tightened fiscal policies. The scope and scale of the macropolicy mix should aim to test the market for necessary adjustments rather than create policy shocks. Considering the evident policy inconsistencies, prudential screening and monitoring should be strengthened to prevent speculative financial activities.
Keywords: E44; E52; F21; F32; 330; Finanzsektor; Finanzmarkt; Kapitalimport; Direktinvestition; Wirtschaftliche Anpassung; Vietnam